2015
DOI: 10.1128/jvi.01482-15
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-Associated Herpesvirus Viral Interferon Regulatory Factor 1 Interacts with a Member of the Interferon-Stimulated Gene 15 Pathway

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) is a gammaherpesvirus known to establish lifelong latency in the human host. We and others have previously shown that three KSHV homologs of cellular interferon regulatory factors (IRFs), known as viral IRFs (vIRFs), participate in evasion of the host interferon (IFN) response. We report that vIRF1 interacts with the cellular interferon-stimulated gene 15 (ISG15) E3 ligase, HERC5, in the context of Toll-like receptor 3 (TLR3) activation and IFN induction. The ISG1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…One proposed mechanism for this was through the regulation of specific KSHV microRNAs that are known to modulate KSHV latency 74 . In a second study, KSHV infection was reactivated in primary effusion lymphoma cells by various means, and both ISG15 and ISG15 conjugate levels were found to be increased, along with activation of the type I interferon system 75 . Knockdown of either ISG15 or the E3 ligase HERC5 resulted in an increase in KSHV reactivation and an increase in the production of infectious virus 75 .…”
Section: Modulation Of Viral Latencymentioning
confidence: 95%
“…One proposed mechanism for this was through the regulation of specific KSHV microRNAs that are known to modulate KSHV latency 74 . In a second study, KSHV infection was reactivated in primary effusion lymphoma cells by various means, and both ISG15 and ISG15 conjugate levels were found to be increased, along with activation of the type I interferon system 75 . Knockdown of either ISG15 or the E3 ligase HERC5 resulted in an increase in KSHV reactivation and an increase in the production of infectious virus 75 .…”
Section: Modulation Of Viral Latencymentioning
confidence: 95%
“…We found that silencing of either ISG15 or ISG20 greatly increased the virion release (there were more Lana transcripts in these infected groups compared to controls) (Figure 3C). Interestingly, one very recent study also reported that silencing of ISG15 in KSHV latently infected iSLK.219 cells resulted in a higher level of virus reactivation and an increase in infectious virus production [20]. They also found that KSHV-encoded vIRF1 protein can inhibit IFN activation in response to viral infection, through interaction with HERC5, an ISG15 E3 ligase, to alter ISG15 modification of cellular proteins [20].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, vIRF1 itself was also a target of ISG15 conjugation. KSHV-infected cells exhibited increased ISG15 conjugation upon reactivation from latency in coordination with increased IFN [20]. …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, among vIRFs, only vIRF1 decreases phosphorylation and nuclear translocation of IRF3 upon TLR3 activation, suggesting that vIRF1 and other vIRFs block TLR3-mediated IFN-β production in different manners (Jacobs et al, 2013). Recently, Jacobs et al (2015) demonstrated that vIRF1 interacts with cellular ISG15 E3 ligase HERC5 and decreases global IS-Glyation in the context of TLR3 activation. Together, these findings suggest that each vIRF may uniquely inhibit the TLR3-mediated antiviral responses.…”
Section: Tlr Signaling Pathwaymentioning
confidence: 99%